Female Employees’ Retention in Hospitality Sectors (Nepalese Journal of Management Research, 2025)
This study explores the critical role of employee retention in the hospitality industry, with a specific focus on retaining female employees. As a key contributor to global and local economies, including Nepal, the hospitality sector depends on a skilled workforce to maintain service quality and operational efficiency. Retaining female employees is crucial for sustaining these standards and enhancing brand reputation. The study highlights the importance of targeted retention strategies addressing both organizational and socio-cultural factors to increase female participation in Nepal’s hospitality sector. Based on primary data collected through a structured questionnaire with 300 respondents in Chitwan district, the study used convenience sampling to gather quantitative data. Independent variables included work-life balance policies, compensation and benefits, career development opportunities, social norms, and cultural expectations, while the dependent variable was female employee retention. Findings reveal that work-life balance policies, compensation and benefits, social norms, and cultural expectations positively influence female employee retention. Conversely, career development opportunities show a negative impact. Work-life balance policies, followed by compensation and benefits, emerged as the most significant factors affecting retention. The study recommends adopting flexible work schedules, enhancing family-friendly initiatives, revising compensation packages, fostering inclusivity, and addressing cultural barriers to improve retention. Regular evaluation of these strategies through surveys and retention analysis is essential for sustained progress.